Pengaruh Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) dan Kepemimpinan Keselamatan terhadap Kinerja Keselamatan di Proyek Hunian Pekerja Pendukung Operational Kampung Susun Bayam (HPPO KSB) di Jakarta - Syakinah, Rohmatun (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Accidents at work in the construction industry recently have caused material losses, deaths, healthproblems, and production disruptions, which are a problem for all parties involved. Occupationalaccidents are often the result of negligence and rule violations, so the government must take joint stepsto prevent and eliminate these incidents. The purpose of this study was to see the effect of the K3Management System (SMK3) and safety leadership on safety performance in the HPPO KSB project. Thisresearch method uses a semi-quantitative cross-sectional nature. A sample of 154 people including topManagement (Project Manager, Deputy Manager, and Construction Manager), middle Management(Site Manager, Supervision, and SHE), and Low Management (Man Power). The research was conductedfrom March to June 2023. Analysis tests used descriptive analysis, validity tests, reliability tests usingCronbach's Alpha, R2 coefficient of determination test, concurrent evaluation (F Test), and hypothesistesting. The results of this research are the occupational safety and health management system projectat HPPO KSB, the significance level is set at p 0.05 (T count = 2.270 > > t table = 1.975). In the KSB HPPOproject the safety leadership increased safety performance to the limit of a t-count value of 3.724> in a ttableof 1.975 and an F value of 0.000 0.05, or 16,502> F. An effective occupational health and safetymanagement system improves project safety records HPPO KSB. Safety leadership in the KSB HPPOProject and influence of the Occupational Safety and Health Management System (SMK3) both helpimprove safety outcomes. Strong safety leadership, together in conjunction with an Occupational Safetyand Health Management System, has been shown to enhance the safety of operations.Keywords: SMK3, HPPO KSB, Leadership